Examining the impact of theraplay interventions within education settings on classroom behaviour and student-teacher relationships for male students aged three to eleven-years-old identified with social, emotional and mental health (SEMH) difficulties: a multiple case study design - Bennion, Kim (2020)
Negative risk factors relating to Social Emotional Mental Health can include educational and later-life difficulties (Tellis-James & Fox, 2017). This suggests more should be done to support young people who are at risk or showing signs of social, emotional and behavioural difficulties (National Institute for Health and Clinical Excellence, 2018) and education settings are one environment that can offer this support (Cefai & Cooper, 2009).